Domes on the eastern margin of the north Cuddapah basin - RAO , V. BHASKARA; SWAMY, G. NARASIMHA (MAUSAM, 1976)
The eastern margin of the north Cuddapah basin is characterised by a singular series of peculiar, ellipsoidal domes from Vinukonda upto the Krishna river in the north. In the Course of the regional magnetic investigations conducted in the north Cuddapah basin and the adjoining areas, it is found that these domes are practically without any expression in the regional anomaly maps. It is suggested that these are probably mere topographic features only, without corresponding reflection in the basement.